DINAMIKA HUKUM ISLAM DI INDONESIA (STUDI ATAS FATWA WAHDAH ISLAMIYAH) - Asmuni Mth; Muntoha Muntoha; Ahmad Arif Syarif (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2015)
Study of the products of Islamic law in Indonesia is often partial and focused on mainstream mass organizations. In fact, the existence of small and local organization that influence the dynamics of Islamic law in Indonesia, such as Wahdah Islamiyah. In response to the problems of the people, especially in South Sulawesi, this organization has been often condemned heretic wing, spreaders heresy and other negative charges. In fact, the style and the formulation of laws formulated emphasizes maqashid al-shari'ah, thus seem more flexible, visible, and dynamic. This negative accusations, is more likely due to political pressure, of the substance of the factors defined legal fatwa. Seeing the dynamic thinking of Islamic laws of community organi zation of Wahdah Islamiyah in its way to formulate some Fatwa by interacting with social, economic, political, cultural, localized, national and global reality is to enforce human beings’ welfare without ignoring nash. The interaction with social reality forms a way of thinking of Wahdah Islamiyah which leads to moderation and inclusive characteristics.